Optimalisasi Penerimaan Pajak Melalui Kegiatan Pengawasan Kepatuhan di KPP Pratama Jakarta Grogol Petamburan - Dwi Martani; Sugiarto, Tri (Owner : Riset dan Jurnal Akuntansi, 2024)
Indonesia's tax ratio is lower compared to some countries in the ASEAN region. Therefore, Directorate-General of Tax needs to create policies in order to increase sustainable tax compliance and optimal tax revenue. This research aims to analyze compulsory tax compliance supervision activities based on the Letter of the Director-General of Tax No. SE-05/PJ/2022 which is consisting of four stages: planning, implementation, follow-up, and evaluation monitoring at the Kantor Pelayanan Pajak Pratama Jakarta Grogol Petamburan using the (OECD, 2021) evaluation criteria consisting of relevance, coherence, effectiveness, efficiency, impact, and sustainability.. The method used in this research is a descriptive qualitative method. The data collection technique is performed using in-depth interviews with 10 respondents as primary data and review documents, regulations, as well as previous research relevant to the research theme as secondary data then perform triangulation of data to check the validity of data or information obtained. The results of this research show that SE-05 supervision activities have been carried out well by achieving tax revenue targets, achieving office assessment indicators, and helping to increase taxpayer compliance. Apart from that, it is hoped that there will be regulations that expand authority and increase the number of account representative personnel. This research is expected to contribute in efforts to increase revenue and compliance with tax obligations.